MICROWAVE PHOTONIC FILTERS BASED ON STIMULATED BRILLOUIN SCATTERING: A REVIEW - Zainab AL-Zaidi; Adnan Sabbar (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Microwave photonic filters (MPFs) based on stimulated Brillouin scattering (SBS) and their applications in various microwave systems are extensively reviewed. This work summarizes the state of the art, emphasizing new methods, experimental proofs, and optimized passband properties of SBS-based MPFs. Important topics include frequency-tuning-range-extended MPFs, switchable MPFs, high-selectivity rectangular filters, and bandwidth-reconfigurable MPFs, addressing significant issues in traditional filters. Photonic technology in microwave photonics (MWP) enables processing of broadband, high-frequency microwave signals with excellent selectivity, stability, and adjustable passband properties. Applications span optical wireless communication, optical signal processing, radio over fiber (RoF) systems, satellite communications, optical sensors, and instrumentation. This review offers valuable insights into the advancements and potential impact of SBS-based MPFs in microwave systems